An investigation of the nature and extent of record keeping by micro financiers in Zimbabwe: a case of KCI Management Consultants - Matsenga, Trymore (Midlands State University, 2019)
The purpose of this study was to investigate the nature and extent of record keeping in microfinance institutions and its effects to their sustainability. The research was influenced by underperformance of microfinance industry as 60% of the industry were not operating profitably while 30 institutions were reportedly shut down operations in 2017. The main objective of this study was to identify the nature of record keeping by microfinance institutions. To achieve the objectives of the study, data was obtained through the use of primary and secondary sources. The target population was 70 and a sample size of 40 respondents was chosen. The study alsopresented empirical evidence and global experiences in terms of record keeping by micro financiers, mutual (2015) and Hilisnki (2017) were the key authors and they cited the consequences of poor record keeping as loss of data, production is negatively affected, legal consequences as well as financial consequences. The findings of the research were presented in the form of graphs, tables and charts. Data analysis revealed that at Checheche KCI the nature of record keeping was poor mainly because they are still using the manual system as well as hiring untrained bookkeepers. The research concluded that KCI still has a long way to go as far as proper record keeping is concerned if they are to make it to the top particularly on areas of default management. The study recommended that KCI should make use of a computerized system, staff training, incentives to employees when targets set are met, regular attendance of workshops held by ZAMFI as well as close supervision to ensure maximum results of proper record keeping.